2021
DOI: 10.1002/bse.2852
|View full text |Cite
|
Sign up to set email alerts
|

Environmental transparency and investors' risk perception: Cross‐country evidence on multinational corporations' sustainability practices and cost of equity

Abstract: We explore whether a greater amount of environmental disclosure can reduce a firm's ex ante cost of equity. This could occur because the quantity of environmental information changes investors' risk perception of the company, thereby influencing its ex ante cost of equity. Our study is a cross-country analysis of 1481 multinational corporations (MNCs) across 43 countries and territories from 2013 to 2019. Firstly, we measure investors' risk perception as a firm's ex ante cost of equity by employing five differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…GDP growth is the annual change of GDP in percentage from the World Bank. We use the World Bank's Worldwide Governance Indicators (WGI) as the proxy for country‐level governance (Orazalin & Mahmood, 2021; Yu et al, 2021). WGI has six indicators, and each indicator ranges from −2.5 weak to 2.5 strong: (1) voice and accountability, (2) political stability and absence of violence/terrorism, (3) government effectiveness, (4) regulatory quality, (5) the rule of law, and (6) control of corruption.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…GDP growth is the annual change of GDP in percentage from the World Bank. We use the World Bank's Worldwide Governance Indicators (WGI) as the proxy for country‐level governance (Orazalin & Mahmood, 2021; Yu et al, 2021). WGI has six indicators, and each indicator ranges from −2.5 weak to 2.5 strong: (1) voice and accountability, (2) political stability and absence of violence/terrorism, (3) government effectiveness, (4) regulatory quality, (5) the rule of law, and (6) control of corruption.…”
Section: Sample and Methodsmentioning
confidence: 99%
“…For instance, Reber et al (2021) found that voluntary CSR disclosures reduce idiosyncratic volatility and downside risk of stock price declines at IPOs. Environmental disclosures, the focus of our study, have been found to decrease information asymmetry and reduce the risk profiles of firms (Benlemlih et al, 2018; Cormier & Magnan, 2015; Yu et al, 2021). However, studies on the relationship between environmental disclosures and post‐IPO returns have produced equivocal results (Huang et al, 2019; Pencle & Mălăescu, 2016).…”
Section: Introductionmentioning
confidence: 92%
“…For instance, Reber et al (2021) found that voluntary CSR disclosures reduce idiosyncratic volatility and downside risk of stock price declines at IPOs. Environmental disclosures, the focus of our study, have been found to decrease information asymmetry and reduce the risk profiles of firms (Benlemlih et al, 2018;Cormier & Magnan, 2015;Yu et al, 2021).…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations